Body weight and healthy diet among elderly Turkish immigrants : links to income - Johanna Buchcik; Joachim Westenhöfer; Annette Beyer; Mary Schmoecker; Christiane Deneke (Ernährungs-Umschau : Forschung & Praxis, 2013)
In the Sag˘lık study, 100 elderly men and women in Germany with a Turkish migrant background were questioned about body weight/body size, their fruit, vegetable and meat consumption and their income, among other things. The results reveal, particularly among women, a lower income and an exceptionally high prevalence of overweight and obesity. There was a significant correlation between lower income and greater body weight. Both men and women consume significantly low amounts of fruit and vegetables, in comparison with recommendations, whereby this consumption increases with higher incomes. There is a clear need for nutritional health promotion measures for the target groups, which to begin with appear more urgent for women than for men.
Keywords: Dietary behaviour; body weight; overweight; obesity; migrants; migrant background; Turkish; income; Ernährungsverhalten; Körpergewicht; Übergewicht; Adipositas; Migranten; Migrationshintergrund; türkisch; Einkommen